2023
DOI: 10.1021/acsapm.3c00309
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Amino Acid Alternating Copolymers with Potent Antibacterial Properties for the Treatment of Periodontitis

Abstract: Although antibacterial peptides with excellent properties emerge endlessly, the antibacterial peptides with alternating structures have not attracted much attention. In this work, three amino acid alternating copolymers (Orn-Ser, Orn-Gly, and Orn-Val) with similar molecular weights but different hydrophilicity were constructed for the study of antibacterial properties through the solid-phase peptide synthesis (SPPS) method. We found that these three amino acid alternating copolymers showed excellent biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Local therapy using drug carriers is gaining immense attention for treating periodontitis. , In particular, drug carriers in the form of biodegradable polymeric microspheres have the capability of filling in the deep periodontal pocket and anatomical complexities of the alveolar bone, thereby reducing the total drug dose, enabling controllable drug release, and exhibiting tailored bioactive property and minimal systemic adverse effects. Xie et al reported a prolonged local antibacterial strategy based on Ag/TiO 2 /alginate (ATA) hydrogel microspheres, which promoted the generation of reactive oxygen species and O 2 under low-level H 2 O 2 to inhibit Porphyromonas gingivalis . In another study, a drug-loading nanocarrier was made by a hydrophobic lipid core (1, 2-distearoyl- sn -glycero-3-phosphoethanolamine-poly­(ethylene glycol) loaded with alpha-lipoic acid and a hydrophilic shell (poly­(amidoamine) dendrimer encapsulating minocycline hydrochloride) .…”
Section: Introductionmentioning
confidence: 99%
“…Local therapy using drug carriers is gaining immense attention for treating periodontitis. , In particular, drug carriers in the form of biodegradable polymeric microspheres have the capability of filling in the deep periodontal pocket and anatomical complexities of the alveolar bone, thereby reducing the total drug dose, enabling controllable drug release, and exhibiting tailored bioactive property and minimal systemic adverse effects. Xie et al reported a prolonged local antibacterial strategy based on Ag/TiO 2 /alginate (ATA) hydrogel microspheres, which promoted the generation of reactive oxygen species and O 2 under low-level H 2 O 2 to inhibit Porphyromonas gingivalis . In another study, a drug-loading nanocarrier was made by a hydrophobic lipid core (1, 2-distearoyl- sn -glycero-3-phosphoethanolamine-poly­(ethylene glycol) loaded with alpha-lipoic acid and a hydrophilic shell (poly­(amidoamine) dendrimer encapsulating minocycline hydrochloride) .…”
Section: Introductionmentioning
confidence: 99%